1995
DOI: 10.1007/bf00241355
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic and kinetic analysis of locomotion during voluntary gait modification in the cat

Abstract: As part of a study to characterize the postural reactions that occur during voluntary gait modification, we examined the kinematic, electromyographic (EMG), and kinetic responses that occurred when cats stepped over an obstacle placed in their path. Analyses of the kinematics as each of the forelimbs stepped over the obstacle showed that changes in joint angles were most pronounced at the elbow of the first (lead) limb, and at the shoulder of the second (trailing) limb. In the hindlimbs, there was a pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…As Massion (1992) has strongly emphasized, these responses are also anticipatory in nature in that they are controlled in a feedforward manner to anticipate the changes produced by the movement. Similar arguments have also been made for the postural responses that accompany modifications of locomotor gait (Lavoie et al 1995;McFadyen and Winter 1991). Following the terminology of GahĂ©ry (1987), we refer to these postural responses in Fig.…”
Section: Anticipatory Postural Adjustments That Accompany the Movementmentioning
confidence: 64%
“…As Massion (1992) has strongly emphasized, these responses are also anticipatory in nature in that they are controlled in a feedforward manner to anticipate the changes produced by the movement. Similar arguments have also been made for the postural responses that accompany modifications of locomotor gait (Lavoie et al 1995;McFadyen and Winter 1991). Following the terminology of GahĂ©ry (1987), we refer to these postural responses in Fig.…”
Section: Anticipatory Postural Adjustments That Accompany the Movementmentioning
confidence: 64%
“…Accordingly, speed-related increases in the amplitude of HL joint angle changes and the level of HL muscle activity are larger in Rhesus (present results) than in cats (Halbertsma et al 1976;Jiang and Drew 1996;Rossignol 1996), particularly in the distal extremities. In the same vein, vertical reaction forces are larger on the FL than the HL during cat locomotion (Manter 1938;Lavoie et al 1995), whereas the inverse ratio characterizes non-human primate stepping (Kimura 1985). Similar to that observed in monkeys, however, the cat HLs provide propelling forces for a longer period than the FLs, and the FLs are used mainly for braking (Lavoie et al 1995).…”
Section: Comparison With Cat Locomotionmentioning
confidence: 99%
“…In the same vein, vertical reaction forces are larger on the FL than the HL during cat locomotion (Manter 1938;Lavoie et al 1995), whereas the inverse ratio characterizes non-human primate stepping (Kimura 1985). Similar to that observed in monkeys, however, the cat HLs provide propelling forces for a longer period than the FLs, and the FLs are used mainly for braking (Lavoie et al 1995). This substantial contribution of HL muscles to body propulsion in Rhesus at higher speeds is reflected in the dramatic modulation of distal muscle activity, such as the FDL and FHL muscles, which is not observed in cats (Fleshman et al 1984;O'Donovan et al 1982).…”
Section: Comparison With Cat Locomotionmentioning
confidence: 99%
“…However, we did not investigate systematically the capacity of these animals to walk voluntarily on specific targets or avoid obstacles that require supraspinal visual inputs. Work in cats (Lavoie et al, 1995;Drew et al, 2008;Farrell et al, 2015) and humans (Patla et al, 1991) has shown the critical importance of direct or indirect cortical mechanisms in controlling precision walking; these mechanisms could participate in the recovery of hemisected cats. We thus developed a repetitive locomotor task that requires some precision walking as previously shown by previous work in a different context and for different needs (Amos et al, 1987;Armstrong and Marple-Horvat, 1996).…”
Section: Introductionmentioning
confidence: 99%